NATIONAL UNITY AND ITS RISKS - Munkhbaatar Purevsuren,; Erdenechimeg Bor, (International Journal of Innovative Technologies in Social Science, 2025)
Mongolians have a long history of prioritizing the growth of their nation, enhancing the well-being of their citizens, and safeguarding the independence of their country through unity. Values such as democracy, freedom, and solidarity are essential for the people to uphold. Despite strong nationalism, without unity, it is ineffective. Experts in politics and social sciences warn that our nation is in danger of losing its national unity and descending into division. This division can be seen in various aspects, including ethnicity, geography, social status, standard of living and education, political and religious beliefs, perspectives, wealth, income, and influence. Therefore, an analysis of the risk factors that threaten national unity is conducted, comparing them to the current challenges facing Mongolia's unity, and some findings are presented.This article highlights the importance of safeguarding our Mongolian national identity from external influences and establishing a cohesive national identity that can withstand present and future challenges. This underscores the immediate need to conduct a comprehensive analysis of the underlying causes, external and internal threats, and influencing factors through the lens of internal security, in order to formulate an effective strategy to counter these threats.